Impact of the Center for communication and digital knowledge on students' university choice: a case study at Hanoi University of Science and Technology; Векторы благополучия: экономика и социум; Т. 53, № 4 - Trinh Thu Thuy; Tran Thị Bích Ngọc; Le Duy Thanh; Barysheva G. A. Galina Anzelmovna (2025, 2025)
The study explores the impact of admissions communication on students’ choices of universities, emphasizing the crucial role of the Center for communication and digital knowledge in providing essential information that helps applicants better understand the majors, study programs, and future career opportunities. The authors used the mixed research methods, including qualitative and quantitative methods; the study analyzed survey results from 500 students at the University of Science and Technology. The findings revealed that students predominantly accessed online admissions communication channels, using them 4.5 times more than offline channels. The information most sought after by students included detailed descriptions of various training programs and career guidance post‐graduation. The impact of online and offline admissions communication channels on students' perceptions and decision‐making in selecting a university was carefully evaluated based on students' feedback regarding specific criteria on a 5‐point Likert scale. A notable aspect of this research is its confirmation that both admissions communication methods complement each other in the context of theory and practice at Hanoi University of Science and Technology. The proposed solutions aim to enhance the quality of recruitment communication for higher education institutions amidst the rapid advancements in digital technology